Risky Sexual Practice and Associated Factors Among Youth Preparatory Students in Gondar City, Northwest Ethiopia - Azene, Zelalem Nigussie; Tsegaye, Lanchisl; W/Gebriel, Mekdes; Tadesse, Adamu; Tadele, Abreham; Aynalem, Getie Lake; Andualem, Zewudu; Taye, Birhan Tsegaw (Frontiers in Public Health, 2022)
Background: Risky sexual practices can negatively affect the health of youths by predisposing them to a variety of sexually transmitted infections including HIV/AIDS and unwanted pregnancy which, in turn, would lead to serious lifelong deleterious health, social, and economic consequences. While youths tend to be less well-informed and require more information, little has been known in Ethiopia. Therefore, this study was aimed to assess the prevalence of risky sexual practices and associated factors among youth students in Gondar city, northwest Ethiopia. Methods: A cross-sectional study was conducted among 414 regularly attending youth students in Gondar city from April to May 2019. A simple random sampling technique was used to select the study participants. Data were collected by using a pre-tested, structured, and self-administered questionnaire. Bivariable and multivariable logistic regression analyses were employed, and a multivariable binary logistic regression model was used to identify the effect of independent variables on the outcome variable at p < 0.05 with its 95% confidence interval. Result: The prevalence of risky sexual practice was 49.3%. Peer pressure (AOR=1.99, 95% CI: 1.21, 3.26), drinking alcohol (AOR=4.88 95% CI: 3.06, 7.79), and watching pornography (AOR= 2.82, 95% CI: 1.74, 4.56) were positively associated with the risky sexual practice of youths. Whereas, age, gender, and pocket money did not have any association with risky sexual practice in this study. Conclusion: In this study, the prevalence of risky sexual practice was found to be high. Thus, multisector collaboration efforts are needed from parents, schools, health facilities, and government to tackle the exposure of in-school youth towards peer pressure, drinking alcohol, and watching pornographic films which in turn helps to bring about healthy sexual practices among them.